Application of Learning Strategy Start with A Question Based on Critical Thinking to Improve Learning Achievement - Antika, Rindi; Fuadi, Salis Irvan (Al Hikmah: Journal of Education, 2022)
This research aims to knowing the implementation strategy of learning starts with a question based on critical thinking, knowing the student’s learning achievement after used learning strategy starts with a question based on critical thinking; and knowing the differencies of learning achievement between the students who uses learning starts with a question strategi based on critical thinking and do not use it.This research used quasi experimental approach, using nonequivalent control group pretest postest design.The result shown that their are a differencies between the students who use. Learning starts with a question strategy based on critical thinking and the student who not use it. This proven by using thitung > ttabel test. At tehe level of significance 1 that is 4,34 > 2, 712. students who use learning starts with a question strategy was improved. Shown by using gain test for experimental class and obtained 0,682 of result.